EXPERIENCE OF APPLYING THE CONCEPT OF HIGH CONSERVATION VALUE FORESTS IN ARMENIA - Ghulijanyan, A. H.; Galstyan, S. R. (Forestry and Forest Melioration, 2018)
Introduction The forests in the Republic of Armenia cover 332,333 thousand ha or 11.17 % of the total territory of the country. The majority of forests are located in the north-eastern regions of Armenia. During the recent decades, the forests in Armenia have been under anthropogenic pressure, which resulted in a reduction of forested areas and degradation of forest ecosystems. Meanwhile, the presence of relatively large undisturbed forest areas is crucial for safeguarding well-functioning ecological processes and provision of important ecosystem services including water and soil protection. They include forests in protected areas and outside. The proper management of such forest areas is a key to have sustainable services and benefits provided by the forest ecosystems. Hence, identification of such forests is the first step towards their maintenance, protection or other respective management action. Materials and Methods A potential high conservation value forest (HCVF) area in Noyemberyan Forest Enterprise (Northern Armenia) was analyzed and assessed by draft national criteria on the identification of HCVF. The data of forest taxation and management plan of Noyemberyan Forest Enterprise were used. The parameters of the forest area were compared to the criteria with thresholds on the identification of HCVFs. Results The concept of high conservation value forests (HCVFs) was introduced by the Forest Stewardship Council in 1999 to maintain and conserve respective forest values. Draft national classification and criteria for identification of HCVFs in Armenia were developed in 2016. The national category HCVFs 2 implies relatively large intact forest areas, which support viable populations of most or all naturally occurring species of plants and animals. A potential HCVF area with the territory of 1563 ha in thе north-eastern Armenia (Tavush Province) was assessed by the national criteria for identification of HCVF 2. The area mainly corresponds to the national criteria and can be defined as HCVF 2. The area should be under focused protection with no intervention measures in the management plan. It is suggested to modify the criterion on the age structure of HCVF 2. The analysis of field taxation data of the forest enterprise, where the assessed territory is located, as well as the experience of the application of the national criteria, shows that there are no other HCVF 2 areas on the territory of the forest enterprise. Such territories will be rare also in the other forests of Armenia. Identification and proper management of HCVF 2 areas are important for Armenia given the ongoing anthropogenic pressure on forests. Conclusions The assessed area mainly corresponds to the national criteria for identification of HCVFs 2 in Armenia. The partial inconsistency is only with the criterion on the presence of maturing, mature and overmature forests, which make only 37.9 % of the forests. Natural forest ecosystems normally consist of the stands with different age classes, which are formed during the long period of natural development without external intervention. Therefore, the formulation of the criterion “maturing, mature and overmature forests” is too strong. It is almost impossible to find such forests. Thus, it is suggested to reformulate the criterion as “the prevalence of stands above 100 years old”, which will show that the forest area has been developing naturally during a long time and should be close to its natural state. 3. There are no more other sites in Noyemberyan Forest Enterprise to correspond to all the national criteria for identification of HCVF 2. Meanwhile, the Forest Enterprise is one of the best in terms of forests and there is a forest sanctuary with the area of 150 ha in the midst of the Forest Enterprise. Most probably there will be no many such areas also in the other forest enterprises of Armenia. Therefore, HCVF 2 areas need special attention and focused protection. In particular, the identified area should be subject to detailed field study and no intervention measures should be envisaged during the update of the management plan.